GW170817 Implementation on Einstein-Gauss-Bonnet Theory with Non Minimal and Non Minimal Derivative Coupling - Fitria Khairunnisa; Getbogi Hikmawan; Freddy Permana Zen (Indonesian Journal of Physics, 2022)
The GW170817 event manifests that gravitational wave velocity is close to thespeed of light. As a result, several theories of gravity are no longer applicable, including EinsteinGauss-Bonnet (EGB) inflation. However, a constraint equation could be applied so that thetheory could produce a viable result. In this study, the EGB inflation is being extended byadding a non-minimal coupling (NMC) and a non-minimal derivative coupling (NMDC). Freeparameters values were evaluated to obtained viability with observational indices. We use powerlaw and exponential Gauss-Bonnet coupling functions. Each model provides observational valuesof ns and r that are compatible with the observations and has its characteristic. It specifiesthe free parameter that controls the alteration of ns and r values. The power-law model iscontrolled by the power m of the Gauss-Bonnet coupling function and the potential integrationconstant, V2. While the exponential model is controlled by the potential integration constant cand the power m of the exponential function. Some approximations do not hold true so that themodels need to be rectified. Apparently, the rectified power-law model is violating null energycondition (NEC), so we also provide the non-violating NEC power-law model.